A new crustacean clam shrimp (Spinicaudata: Eosestheriidae) from the Upper Triassic of Argentina and its importance for 'conchostracan' taxonomy - Gallego, Oscar Florencio (Alcheringa: An Australasian Journal of Palaeontology)
A new species of a fossil crustacean clam shrimp (Spinicaudata: Eosestheriidae) Menucoestheria wichmanni is described from the lower Upper Triassic Vera Formation (Los Menucos Complex) in Rio Negro Province, southern Argentina. This discovery represents the first record of this family in the Triassic of Argentina and the southernmost record of South American Triassic 'conchostracans' (Spinicaudata). The new species shows close affinities with Middle Jurassic faunas from Antarctica and offers important data on the taxonomy (notably the use of ornamentation characters), palaeobiogeography (as South America hosts the oldest-known fossils of this family) and evolution of the Gondwanan faunas. Other South American eosestheriid species are tentatively recognized. Menucoestheria is hypothesized to be the ancestral form of the Triassic-Jurassic Gondwanan eosestheriids. Relationships between European and Gondwanan eosestheriids remain unresolved. © 2010 Association of Australasian Palaeontologists. Fil: Gallego, Oscar Florencio. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Nordeste. Centro de Ecología Aplicada del Litoral. Universidad Nacional del Nordeste. Centro de Ecología Aplicada del Litoral; Argentina